Effects of the training status on the hormonal response and recovery from high-intensity isokinetic exercise: comparisons between endurance-trained athletes and sedentary subjects - Minetto, M. A.; Paccotti, P.; Borrione, P.; Massazza, G.; Ventura, M.; Termine, A.; Di Luigi, L.; Pigozzi, F.; Angeli, A. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: Aims of the study were: to determine the differences in the mechanical, hormonal and lactate responses to a high-intensity isokinetic exercise in two groups of endurance-trained athletes (EA, n=11) and sedentary subjects (SED, n=11); to evaluate the relationships between the hormonal and lactate responses; to evaluate the effects of the training status on the pituitary responsiveness to the exercise. Methods: EA and SED completed, for each leg, 4 sets of 20 maximal concentric contractions of the knee extensor muscle groups at 180° s-1 angular velocity. Blood and saliva for hormonal and lactate determinations were sampled before, immediately after the test and during the subsequent recovery of 2 hours. Results: The exercise was completed by all subjects and elicited significant mechanical and biochemical responses both in EA and in SED subjects. No differences were found between the two groups both in the mechanical performances and in the increases of lactate and hormones of the pituitary-adrenal axis or in the comparison of the slopes of adrenocorticotropic hormone (ACTH), cortisol, and dehydroepiandrosterone recovery after the peak. The correlation analyses showed significant positive relationships between lactate peak values and percentages of change for ACTH (r2=0.16, P<0.05), salivary cortisol (r2=0.42, P<0.01), and serum cortisol (r2=0.56, P<0.001). Conclusions: The adrenocortical activation was found, in this particular setting, at least partly dependent on the muscular lactate production, while no effect of the training status on the pituitary responsiveness to exercise was evident, as it was indirectly confirmed by no abnormalities in the rates of hormonal recovery after the exercise session.